Students' perceptions of alternative history as a learning tool: a case analysis in 4th ESO (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2023)
The most recent research in history education has highlighted the importance of the development of historical thinking as a basis for teaching the subject. With this in mind, this paper sets out to investigate students' perceptions of the use of counterfactual history as a learning tool, aimed at improving the acquisition of skills associated with historical thinking, as well as stimulating their motivation. For this purpose, a qualitative research and case analysis of a group of 16 students of 4th ESO has been chosen to explore the perceptions of the participants through a semi-structured questionnaire based on a content analysis. The results show the students' perceptions of alternative history in terms of content comprehension, competence development and increased motivation. In this sense, and despite the difficulties they may encounter, alternative history as a didactic tool can be a complementary practice of great interest for the understanding and learning of history.
Keywords: critical sense; secondary education; qualitative research; didactics